Examining factors affecting the failure of Khofifah Indar Parawansa in East Java gubernatorial elections - Wahidah Zein Br Siregar (Masyarakat, Kebudayaan dan Politik, 2021)
Statistics consistently show that women in executive political leadership positions are much lower than men at a global level. Institutional, socio-economic, and socio-cultural factors influence this condition. Some studies also identified that media considered as an essential factor for women’s involvement in politics. This paper examines factors contributing to the failure of Khofifah Indar Parawansa in East Java gubernatorial elections and whether or not gender is a matter in affecting the failure. This research analyzed kompas.com on how media reports the process of exploring this issue, how it frames the factors and the result of the 2008 and 2013. Seventy-nine news reports from online newspapers, 27 from the 2008 election and 52 from the 2013 election, were analyzed. Researchers traced these articles using thematic textual analysis to identify factors inhibiting Khofifah’s participation in the elections. The media reported that political, socio-economic, and socio-cultural aspects inhibited her success in the elections. Interestingly, the media emphasizes the political aspect as the most significant factor in her failures. It implies that the media provides balanced and fair information on female candidates.